Carcass Traits and Meat Quality of Prestice Black-Pied Pig Breed - Václav Matoušek; Naděžda Kernerová; Klára Hyšplerová; Dana Jirotková; Michaela Brzáková (Asian-Australasian Journal of Animal Sciences, 2016)
The objective of the study was to evaluate fattening performance, carcass value and meat quality in pigs of Prestice Black-Pied breed in relation to slaughter weight (SW) and gender (barrows and gilts, resp.). Pigs were divided into weight categories: SW1 (75 to 99.9 kg), SW2 (100 to 109.9 kg) and SW3 (110 to 130 kg) and all individual traits were analyzed by the general linear model procedure (SAS 9.3). Average SW of each weight group was as follows: SW1 94.2 kg, SW2 105.8 kg, and SW3 115.2 kg. Differences among average backfat thickness of 36.07 mm in SW1, 40.16 mm in SW2, and 43.21 mm in SW3 were significant (p<0.01). Lean meat content was 48.94% (SW1), 48.78% (SW2), and 48.76% (SW3). Pigs were slaughtered at average weight of 105.7 kg for barrows and 104.4 kg for gilts. Average backfat thickness for barrows was 40.90 mm and 38.72 mm for gilts (significant difference p<0.05). Lean meat content was 48.75% in barrows and 48.91% in gilts. The values of pH45, characterizing the meat of very good quality. The loin in SW3 was darker than the muscles of SW1 and SW2. Drip loss was the lowest in SW1 (1.96%), compared to the highest drip loss in SW3 (2.59%). Content of intramuscular fat was 2.68% in SW3, 2.79% in SW2, and SW1 had the lowest content 2.47%. The values of pH45, colour lightness and drip loss were similar in both genders. However barrows had higher intramuscular fat content by 0.31% than gilts (p<0.05).